« Comme l'odeur de la fleur ou le goût du vin » - László, Tímea (Verbum – Analecta Neolatina, 2013)
The article undertakes the task to compare the prosodic features of French and Hungarian. We will consider the manifestations and characteristics of the rhythm, stress and intonation of the two languages. The paper briefly reviews phonetic theories, linguistic definitions and provides poetic examples for the presentation of the musicality of the languages, and offers methodological means to understand and correct prosodic mistakes. Rhythm, stress and intonation as illustrated by poems, dialogues and gestures are remembered more easily. The article would like make teachers aware of the importance of teaching prosodic elements.